Will the mRNA vaccines interfere with Oneâs DNA? - Mohd Nordin, Musa; Musa, Husna (Ibn Sina Medical College, 2021)
As the number of COVID-19 cases continues to rise with over 65 million recorded cases and more than 1.5 million mortalities as of early December, the race against time to find a vaccine intensifies. In recent years, there has been growing interest in mRNA-based technology for the development of prophylactic vaccines against infectious diseases and even for cancers and allergies. The prospects for mRNA vaccines are very promising because of their high potency, capacity for rapid development and potential for low-cost manufacture and safe administration. However, until now, no vaccines using this technology have made it this far in clinical trials thus there have been concerns on the therapeutic and possible adverse effects and claims especially on social media that the vaccines will alter the DNA. This article discusses the unique attributes of mRNA vaccines and current challenges and expectations within the context of the COVID-19 pandemic.